2013
DOI: 10.1111/dth.12086
|View full text |Cite
|
Sign up to set email alerts
|

Acitretin

Abstract: Acitretin, a synthetic retinoid, is the pharmacologically active metabolite of etretinate. It is currently approved by the US Food and Drug Administration for the treatment of severe psoriasis in adults and has been established as a second-line therapy for the treatment of psoriasis resistant to the use of topical therapy. It is also an option for generalized pustular psoriasis, palmoplantar pustulosis, exfoliative erythrodermic psoriasis, and severe psoriasis in the setting of acitretin. It also has been show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 82 publications
2
44
0
3
Order By: Relevance
“…Acitretin, an FDA-approved retinoic acid derivative used to treat psoriasis (Ortiz et al, 2013), was recently shown to reactivate latent HIV and induce the selective apoptosis of HIV latently infected cells in vitro (Li et al, 2016). In the study by Li et al, acitretin induced HIV expression in latently infected T-cell lines and preferential death of HIV infected cells compared to uninfected samples.…”
Section: Pro-apoptotic Compounds To Clear Hiv Latently Infected T-cellsmentioning
confidence: 99%
“…Acitretin, an FDA-approved retinoic acid derivative used to treat psoriasis (Ortiz et al, 2013), was recently shown to reactivate latent HIV and induce the selective apoptosis of HIV latently infected cells in vitro (Li et al, 2016). In the study by Li et al, acitretin induced HIV expression in latently infected T-cell lines and preferential death of HIV infected cells compared to uninfected samples.…”
Section: Pro-apoptotic Compounds To Clear Hiv Latently Infected T-cellsmentioning
confidence: 99%
“…Both, RAR alpha and beta are capable of inducing human ADAM10 promoter activity (Tippmann et al, 2009). Moreover, the commercially available drug acitretin which intracellularly liberates retinoic acid (Ortiz et al, 2013), shifts APP processing in AD model mice toward the alpha-secretase cleavage pathway (Tippmann et al, 2009). The neuroprotective property of RARalpha agonists has been shown in cortical cultures, an AD mouse model (Tg2576 mice) (Jarvis et al, 2010), as well as in hippocampal tissue of aged SAMP8 mice (Kitaoka et al, 2013).…”
Section: Regulation Of Adam10mentioning
confidence: 99%
“…A new analog 194 of the antipsoriatic drug Acitretin was used as a starting compound in the synthesis of pyrrolo[1,2‐ a ]indole 195 . Its cyclization under the action of trifluoroacetic acid leads to pyrrolo[1,2‐ a ]indol‐3‐one 195 (Scheme ).…”
Section: Introductionmentioning
confidence: 99%